Executing Magic in the Modern Era - Davies, Owen. author. aut Link
VII, 118 p.
Keywords: This book is open access under a CC BY 4.0 license This book explores the magical and medical history of executions from the eighteenth to the early twentieth century by looking at the afterlife potency of criminal corpses, the healing activities of the executioner, and the magic of the gallows site. The use of corpses in medicine and magic has been recorded back into antiquity. The lacerated bodies of Roman gladiators were used as a source of curative blood, for instance. In early modern Europe, a great trade opened up in ancient Egyptian mummies and the fat of executed criminals, plundered as medicinal cure-alls. However, this is the first book to consider the demand for the blood of the executed, the desire for human fat, the resort to the hanged man’s hand, and the trade in hanging rope in the modern era. It ends by look at the spiritual afterlife of dead criminals.